Climate changes and adaption policies in the Baltic and the Adriatic regions - Branko Bosnjakovic; Iva Mrsa Haber (UTMS Journal of Economics, 2015)
This paper provides an overview of differences and similarities of the current climate changes in the Baltic and Adriatic coastal regions and appropriate adaptation policies on national, regional and European level. All reparian countries are at different stages of developing and implementing national adaptation strategies. The proposal for an overall BSR wide Climate Change Adaptation Strategy and Action Plan has been launched with the aim to recommend actions for climate change adaptation in the Baltic region. No similar agreement has been concluded yet on the protection of the semi-closed Adriatic Sea, the surface of which is about 1/2 of that of the Baltic Sea, and whose coastal region is home to about 1/4 of that of the Baltic Sea. The differences in the socio-economic characteristics and indicators may be partly responsible for the differring attitudes, actions and reporting concerning the adaptation to climate change, both between individual countries, as well as between the two regions as a whole.
Keywords: O13; P28; Q5; 330; Baltic Sea; Adriatic Sea; climate changes; adaptation instruments